1996
DOI: 10.1097/00006454-199607000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Risk of infection with hepatitis A, B or C, cytomegalovirus, varicella or measles among child care providers

Abstract: The anti-HAV prevalence among US-born providers was low, and seropositivity was not associated with employment characteristics, indicating that occupational exposure to HAV is uncommon under non-outbreak circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 14 publications
2
18
0
4
Order By: Relevance
“…2,7 Serologic surveys of child care workers have not found an increased prevalence of anti-HAV compared with an appropriate comparison group. 8,9 Our investigation supports previous findings 10,11 indicating that the presence of young children in diapers is a factor that may facilitate the spread of HAV in child care centers. Behavioral and environmental factors associated with diaper-wearing children may facilitate the transmission of infectious diseases.…”
Section: Discussionsupporting
confidence: 90%
“…2,7 Serologic surveys of child care workers have not found an increased prevalence of anti-HAV compared with an appropriate comparison group. 8,9 Our investigation supports previous findings 10,11 indicating that the presence of young children in diapers is a factor that may facilitate the spread of HAV in child care centers. Behavioral and environmental factors associated with diaper-wearing children may facilitate the transmission of infectious diseases.…”
Section: Discussionsupporting
confidence: 90%
“…years of day care employment [8] and increased frequency of diaper changing [10]. Although these studies have suggested an occupational risk of day care employment, methodological limitations such as the use of convenience samples decrease the validity of these results.…”
Section: Introductionmentioning
confidence: 99%
“…12 In child care center outbreaks, contact with feces and subsequent personal contact are important means by which transmission occurs, and cases have occurred in child care center workers and household members of children who attend the center. 18,19 Foodborne hepatitis A transmission can occur from food that is contaminated during preparation by an infected food handler (foods not cooked after handling, such as salads and sandwiches) or during growing or processing (eg, produce), but this mode of transmission accounts for a relatively small proportion of reported hepatitis A cases in the United States. 20 Waterborne outbreaks are rare in developed countries with adequate sanitation systems.…”
Section: Figurementioning
confidence: 99%